SOCIAL WORK FOR CHILDREN - Isoqjon Negmatov (Galaxy International Interdisciplinary Research Journal, 2022)
The article makes some comments on the fact that a social worker working with children deals with a wide range of district issues. In particular, the protection of a child who has been abused and neglected among them, the placement of children left without parental care (for example, adoption, foster care for children); support the child in various critical situations in the family (for example, adoption, foster care for children); child support services in various critical situations in the family (for example, relocation, death of a family member, natural disaster, etc.). It has also been suggested that social work with children is one of the most difficult tasks